2008
DOI: 10.1590/s1516-18462008000200008
|View full text |Cite
|
Sign up to set email alerts
|

Mastigação e dietas alimentares para redução de peso

Abstract: OBJETIVO: conhecer as orientações sobre mastigação fornecida por acadêmicos de Nutrição a pacientes submetidos à dieta para redução de peso e verificar os padrões mastigatórios de indivíduos que tenham recebido tais orientações. MÉTODOS: aplicação de questionário a 30 acadêmicos sobre as orientações ministradas no caso de perda de peso e de protocolo de avaliação da mastigação em 30 pacientes em dieta alimentar. Os dados foram coletados em três clínicas escolas da Grande Vitória e analisados por meio do Teste … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
7

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 7 publications
0
3
0
7
Order By: Relevance
“…Under normal physiological conditions, food is eaten after the perception of hunger and eating ceases when the feeling of satiety is achieved / reached 22 . Thus, food intake and energy expenditure are regulated by the hypothalamic region of the brain, which is also responsible for the expression of appetite which is chemically codified in this area 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Under normal physiological conditions, food is eaten after the perception of hunger and eating ceases when the feeling of satiety is achieved / reached 22 . Thus, food intake and energy expenditure are regulated by the hypothalamic region of the brain, which is also responsible for the expression of appetite which is chemically codified in this area 2 .…”
Section: Discussionmentioning
confidence: 99%
“…However, in recent years with the emergence of studies that demonstrate the importance of this activity, both in reducing and maintaining weight 23 , the speech therapist work has been recognized and respected. There are still many issues that need to be researched and published by speech therapists, but with the evidence already found it becomes easier the emergence of more research in the field .…”
Section: Discussionmentioning
confidence: 99%
“…However, little is surveyed on the influence of mastication in the process of weight reduction. Apolinário, Moraes and Motta [23] in the study involving the masticatory evaluation of 30 patients on the diet, reported that the guidelines on chewing are made in most of guidelines with emphasis on the speed and number of chewing cycles. They added that there is adaptation of the masticatory process, despite the unilateral mastication having been much noted.…”
Section: Discussionmentioning
confidence: 99%